2018
DOI: 10.1021/acs.est.8b00967
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review of Eutrophication Models for Life Cycle Assessment

Abstract: This paper evaluates the current state of life cycle impact assessment (LCIA) methods used to estimate potential eutrophication impacts in freshwater and marine ecosystems and presents a critical review of the underlying surface water quality, watershed, marine, and air fate and transport (F&T) models. Using a criteria rubric, we assess the potential of each method and model to contribute to further refinements of life cycle assessment (LCA) eutrophication mechanisms and nutrient transformation processes as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 82 publications
0
44
0
1
Order By: Relevance
“…This variety of approaches demonstrates that there is not a consistent and correct way to account for eutrophication potential across studies. This problem is largely a result of the difficulty and ambiguity in delineating a clear system boundary for an agricultural production system (Morelli et al, 2018). There is a tendency to shrink system boundaries rather than expand them, as this allows for easier data collection and more certainty in the assessment performed.…”
Section: Beyond the Farmmentioning
confidence: 99%
See 1 more Smart Citation
“…This variety of approaches demonstrates that there is not a consistent and correct way to account for eutrophication potential across studies. This problem is largely a result of the difficulty and ambiguity in delineating a clear system boundary for an agricultural production system (Morelli et al, 2018). There is a tendency to shrink system boundaries rather than expand them, as this allows for easier data collection and more certainty in the assessment performed.…”
Section: Beyond the Farmmentioning
confidence: 99%
“…Addressing geospatial variability in LCA may be improved by the utilization of fate and transport models to estimate how inputs are dispersed in the surrounding ecosystem (Morelli et al 2018). However, the application of fate and transport models to current practices will only point out hotspots for implementation of best management, not assist with resolving differences between efficiency and resilience.…”
Section: Fate and Transport Modelingmentioning
confidence: 99%
“…Es por ello que a la hora de evaluar los impactos es necesario contar con factores que caractericen el efecto potencial que la intervención ambiental tiene en un sitio y no en otro. Asimismo, para garantizar que los resultados de un ACV sean coherentes, los métodos y sus modelos deben actualizarse continuamente y la tendencia es regionalizar CFs (Morelli et al, 2018;Civit, 2009;Potting & Hauschild, 2006).…”
Section: Desarrollounclassified
“…Since the 1960s, excess nutrients have been discharged into aquatic environments due to the anthropogenic activities, leading to eutrophication in aquatic environments worldwide [7,8]. Eutrophication has been recognized as one of the major threats to global aquatic ecosystems [9]. Previous studies in assessment of global rivers indicated that nutrients and pathogens were two principal categories of human-induced pollutants within rivers [1].…”
Section: Introductionmentioning
confidence: 99%